PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 49 TAMERAN KECAMATAN BENGKALIS KABUPATEN BENGKALIS - Mimi Afrianti; Lazim N '; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research is the weakness of student’s learning result of science subject. It show from 23 student’s, 8 student’s (34,78%) have lower score, and it is only 15 student’s (65,22%) have average score 65,49. The KKM of this school is 70. According to that problem, the research by implementing of direct instruction model. In cycle I, the percentage of the teachers activity in first meeting is adquate 55%. In second meeting, teachers activity significantly increased to65% with good category. In cycle 2, first meeting was in good category 80% and second meeting indicated a very good category 85%. Meanwhile, the activity of student’s also improved. In cycle 1 indicated 60% in adequate category and in cycle 2 has increased up to 65% with good category. In cycle 2, first meeting, the activity of student’s has been increasing to 75% with good category and second meeting indicated very good category 85%. An average score of student’s learning result before implementation is 65,49. It increased to 69,13 in cycle 1, and 81,52 in cycle 2. In conclussion, implementation of direct instruction model can improve student’s of SD Negeri 49 Tameran kecamatan Bengkalis Kabupaten Bengkalis. Keywords: direct instruction model, Learning result of science subject